Study on proanthocyanidins crosslinked collagen membrane for guided bone tissue regeneration. (March 2021) - Yang, Hongfa; Liu, Wai-Ching; Liu, Xinrui; Li, Yunqian; Lin, Chingpo; Lin, Yu-Min; Wang, An-Ni; Nguyen, Thu-Trang; Lin, Yu-Chien; Chung, Ren-Jei
The goal of this study is to understand the ability of a newly developed barrier membrane to enhance bone tissue regeneration. Here in this study we present the in vitro characterization of the barrier membrane made from type I collagen and crosslinked by oligomeric proanthocyanidins (OPCs). The effects of the membrane (P-C film) on cell cycle, proliferation, alkaline phosphatase activity, and mineralization were evaluated using the human osteoblast cell line MG-63, while the barrier ability was examined using MG-63 cells, as well as the human skin fibroblast cell line WS-1. The pore size is one of the factors that plays a key role in tissue regeneration, therefore, we evaluated the pore size of the membrane using a capillary flow porometer. Our results showed that the mean pore size of the P-C film was approximately 7–9 µm, the size known to inhibit cell migration across the membrane. The P-C film also demonstrated excellent cell viability and good biocompatibility, since the cell number increased with time, with MG-63 cells proliferating faster on the P-C film than in the cell culture flask. Furthermore, the P-C film promoted osteoblast differentiation, resulting in higher alkaline phosphatase activity and mineralization. Therefore, our results suggest that this P-C film has a great potential to be used in guided bone regeneration during periodontal regeneration and bone tissue engineering.